Implementing greenhouse gas trading in Europe: Lessons from economic theory and international experiences - Catherine Boemare; Philippe Quirion (Fondazione Eni Enrico Mattei (FEEM), 2002)
The European Commission (2001a) has recently presented a directive proposal to the Parliament and the Council in order to implement a tradable permits scheme. However, as stressed by the positive political economy, due to the influence of various interest groups, very few environmental policies are implemented in their textbook forms. A close look at implemented emission trading schemes, stressing their discrepancies with textbook requests, is thus useful to increase the chances of forthcoming emission trading schemes to go through the political process without being watered down. We thus review ten emission trading systems, that are either implemented or at an advanced stage of the policy process. We draw attention to major points to be aware of when designing an emission trading system: participants, spatial coverage, permits allocation, temporal flexibility, trading organisation, monitoring, enforcement, compliance, and the harmonisation vs. subsidiarity issue. The aim is to evaluate how far experiences in emission trading move away from theory and why. We then provide some lessons and recommendations on how to implement a greenhouse gas emission trading program in Europe. A review of the theoretical and applied literature, and some interviews, lead us to the assessment of the European system.
Keywords: D78; Q25; Q28; Q48; 330; Emissions trading; climate change policy; policy-making and implementation; Klimaschutz; Emissionshandel; EU-Staaten; Emissionshandel